Research of electric car dynamics - Lyutenko, Vasyl; Nesterenko, Mykola; Durachenko, Hryhoriy; Nesterenko, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2019)
Recently, electric vehicles are becoming widespread throughout the world, so the research is relevant. The results of performed researches of dynamics electric car on the basis of ZAZ-1102 are presented. The calculation method of dynamic loads in electric and mechanical systems of electric cars is developed. The technique considers the electromagnetic processes in the engine, the elasticity of the elastic parts, the oscillatory processes, and damping in the elastic links. On the basis of the developed mathematical model and using the mathematical software apparatus MathCAD, calculations of transients in the electric and mechanical systems have been obtained, based on the obtained results of the research, the constructed graphs. The obtained results of the study of the electric motor drive mechanism can be used for designing, calculating and determining the dynamic loads of electric cars and their hybrids.